2015
DOI: 10.1049/el.2015.1803
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐1100 nm lasing from post‐growth intermixed InAs/GaAs quantum‐dot lasers

Abstract: Impurity free vacancy disordering induced highly intermixed InAs/ GaAs quantum-dot lasers are reported with high internal quantum efficiency (>89%). The lasers are shown to retain the device characteristics after intermixing and emitting in the important wavelength of ∼1070-1190 nm. The non-coated facet Fabry-Pērot post-growth wavelength tuned lasers exhibits high-power (>1.4W) and high-gain (∼50 cm −1), suitable for applications in frequency doubled greenyellow-orange laser realisation, gas sensing, metrology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As we can see from spectral results discussed above, the intermixing effect is significant in determining the emission behaviors of the self-assembled InAs/GaAs QD system. Actually, it has been found that well-controlled QD intermixing allows tuning of their emission wavelength, making it an attractive tool for the manufacturing of multiple-section photonic integrated circuits. ,, However, a desirable large blue-shift of the emission wavelength is always accompanied by a dramatic decrease of PL intensity during the intermixing process. ,, , In addition, the high-quality AlGaAs cladding layer usually is grown at much higher temperatures compared with that for the growth of the QD active medium, which can be equivalent to a relatively strong RTA treatment for the QD active region. Moreover, RTA can also be utilized to get rid of the point defects that are produced during the epitaxy growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we can see from spectral results discussed above, the intermixing effect is significant in determining the emission behaviors of the self-assembled InAs/GaAs QD system. Actually, it has been found that well-controlled QD intermixing allows tuning of their emission wavelength, making it an attractive tool for the manufacturing of multiple-section photonic integrated circuits. ,, However, a desirable large blue-shift of the emission wavelength is always accompanied by a dramatic decrease of PL intensity during the intermixing process. ,, , In addition, the high-quality AlGaAs cladding layer usually is grown at much higher temperatures compared with that for the growth of the QD active medium, which can be equivalent to a relatively strong RTA treatment for the QD active region. Moreover, RTA can also be utilized to get rid of the point defects that are produced during the epitaxy growth.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, it has been found that well-controlled QD intermixing allows tuning of their emission wavelength, making it an attractive tool for the manufacturing of multiple-section photonic integrated circuits. 22,61,62 However, a desirable large blue-shift of the emission wavelength is always accompanied by a dramatic decrease of PL intensity during the intermixing process. 23,26,[58][59][60]63 In addition, the high-quality AlGaAs cladding layer usually is grown at much higher temperatures compared with that for the growth of the QD active medium, which can be equivalent to a relatively strong RTA treatment for the QD active region.…”
Section: ■ Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negligible wavelength shift was observed for devices capped with plasma-enhanced chemical vapor deposition (PECVD) -deposited HfO 2 and SiO 2 dielectric films. [11][12][13] In this work, thermally induced dielectric strain is employed on tensile-strained InGaP/InAlGaP laser structure to promote interdiffusion via application of a single (SiO 2 , Si 3 N 4 ) and bilayers (SiO 2 /Si 3 N 4 ) of dielectric films at elevated temperature. A bandgap blueshift as large as large as 250-300meV was observed for samples capped with a single layer of 1µm-SiO2 and 0.1µm-Si3N4 and annealed at an elevated temperature for cycles of annealing steps.…”
Section: Introductionmentioning
confidence: 99%